THE EFFECT OF NITROGEN FERTILIZATION ON TILLERING AND COMPONENTS OF YIELD IN WHEAT - Sawhney, .Jagdev S (The Libyan Journal of Agriculture, 2023)
Two vulgare types and one durum type of wheat under five rates of nitrogen fertilization were compared for different components of grain yield. Tillering and spike population were found to be related and were affected by nitrogen fertilization. Grain number and grain wt. were also related to each other. More spikelets did not increase grain wt. per spike or per plot ( grain yield ). Medium nitrogen rates produced heavier spikes than high rates. Sedi Mesri 1 appears to be the highest yielding variety under high rates of nitrogen.